Zur Bedeutung jüdischer Exegese der Hebräischen Bibel für christliche Theologie - Grohmann, Marianne (Evangelische Theologie, 2017)
The article analyses the interaction between the Protestant »principle of Scripture«, historical critical exegesis and Jewish interpretations of the Hebrew Bible. The goal of historical critical exegesis of interpreting biblical texts as precisely as possible within their historical and literary contexts is fundamental for the Jewish-Christian dialogue. The plurality of Jewish interpretations of the Hebrew Bible is presented by means of their hermeneutical principles. The article emphasizes the relevance of Jewish biblical interpretation for both Old Testament exegesis and Christian theology, exemplified through different readings of Exod 33:17-23.